Pengaruh Kinerja Keuangan, Ukuran Perusahaan dan Capital Intensity terhadap Agresivitas Pajak - Febrian, Aldira Zahra; Purwatiningsih, Purwatiningsih (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Tax aggressiveness has become a critical issue in corporate governance and public finance, as companies increasingly seek strategies to minimize their tax burdens. Understanding the factors that influence tax aggressiveness is essential for policymakers, regulators, and stakeholders to ensure fair tax compliance and effective fiscal management. This study aims to examine the impact of financial performance, company size, and capital intensity on tax aggressiveness among industrial sector companies listed on the Indonesia Stock Exchange during the period 2019–2023. Employing a quantitative associative research design, the study utilizes purposive sampling to select 75 financial reports from a population of 67 companies. Multiple linear regression analysis is conducted using EViews 12 to analyze the data. The results indicate that profitability and liquidity, as proxies of financial performance, significantly influence tax aggressiveness, suggesting that financially sound companies actively manage their tax obligations to optimize cash flow and earnings. Conversely, leverage, company size, and capital intensity do not show a significant effect, implying that debt levels, organizational scale, and asset structure are less critical in driving tax strategies. These findings emphasize the importance of internal financial health over external factors in shaping tax behavior. Policymakers and regulators are advised to focus on profitability and liquidity indicators to better detect and regulate aggressive tax practices.